SoCap YMH - youth mental health, social capital and help-seeking: a study protocol - Mikael G. Ahlborg; Antony Morgan; Petra Svedberg; Jens M. Nygren; Malin Eriksson; Katrin Häggström Westberg (Frontiers Media S.A., 2024)
BackgroundThe increase in adolescents reporting mental health problems presents a major public health challenge. The complex association between mental health and social capital motivates further investigation of social capital as a crucial aspect in shaping adolescents' help-seeking knowledge, attitudes, and behaviours.AimThis protocol presents a project that aims to investigate social capital in relation to help-seeking and mental health in close collaboration with adolescents and key stakeholders in the school setting, in the southern part of Sweden.MethodsA mixed-method design with three interconnected work packages (WP) will be undertaken with an emphasis on co-production where adolescents are involved throughout the process. WP1 is a development and validation of two questionnaire instruments for assessing social capital and help-seeking in adolescence. WP2 is a longitudinal quantitative study involving 1,500 adolescents from two regions representing rural and suburban/urban settings. Adolescents aged 15 will be asked to complete questionnaires concerning social capital, mental health, and help-seeking in a baseline and one-year follow-up, allowing for investigation of the role of social capital for help-seeking. WP3 is designed to elucidate experiences and knowledge of adolescents and key stakeholders via collaborative World Café workshops. These will be held along the project to evolve the generated knowledge and maximize it's applicability during and after the project is finalized.ConclusionThe results are expected to further the understanding of the relationship between adolescents' social capital, mental health, and help-seeking, to contribute to a deeper understanding of the mechanisms behind the paradoxical help-seeking patterns among adolescents today and to narrow the gap between research and practice to produce sustainable and efficient strategies, which may facilitate help-seeking and improve the mental health of adolescents within existing organizational structures.